The Effect of Working Capital Turnover and Current Ratio on Return on Assets at PT. Kalbe Farma Tbk for the Period 2014-2023 - Yandra, Iin Syofia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The purpose of this study was to determine the effect of Working Capital Turnover and Current Ratio on Return on Assets at PT. Kalbe Farma Tbk Period 2014-2023 either partially or simultaneously. The independent variables in this study are Working Capital Turnover and Current Ratio. The dependent variable is Return on Assets. The type of research is descriptive quantitative using secondary data from the 2014-2023 of the balance sheet and income statement of PT. Kalbe Farma Tbk. The data analysis technique used descriptive statistics, multiple linear regression analysis, hypothesis testing, and coefficient of determination analysis, using the program of SPSS version 26. The results of the hypothesis test show that Working Capital Turnover has a significant effect on Return on Assets, Current Ratio has no significant effect on Return on Assets. Simultaneously, Working Capital Turnover and Current Ratio have a significant effect on Return on Assets at PT. Kalbe Farma Tbk for the period 2014-2023. Analysis of the coefficient of determination (adjusted R2) that Working Capital Turnover and Current Ratio contributed 69,4% to Return on Assets, and the remaining 30.6% was explained by other variables which were not examined in this research.